Sweat-induced skin disorders in athletes: The overlooked role of hyperhidrosis - Białowąs, Patrycja; Zięba, Natalia; Czapiński, Olgierd; Tomicka, Ewa; Knapik, Anna; Ciesielski, Maciej (Quality in Sport, 2026)
Background. Hyperhidrosis is a chronic disorder characterized by excessive sweating that impairs epidermal barrier function and increases the risk of infectious, inflammatory, and friction-related dermatoses, particularly in athletes. Aim. To summarize current evidence on hyperhidrosis-associated dermatoses in athletes, including their pathophysiology, clinical features, diagnosis, treatment, and prevention. Material and Methods. A narrative review of the literature was performed, focusing on sweat-related skin disorders, epidermal barrier dysfunction, diagnostic methods, therapeutic options, and preventive strategies in physically active individuals. Results. Hyperhidrosis promotes epidermal barrier disruption, microbial colonization, and predisposes athletes to fungal, bacterial, inflammatory, and mechanical dermatoses. Diagnosis is primarily clinical, supported by validated assessment tools. Management includes topical aluminum chloride, iontophoresis, botulinum toxin, systemic therapy in selected cases, and preventive measures such as moisture control, hygiene, and appropriate sportswear. Conclusion. Hyperhidrosis should be regarded as a modifiable risk factor for skin disease in athletes. Early recognition, effective treatment, and preventive interventions are essential to reduce recurrent dermatoses and maintain skin health.